Cooperative advertising programs: are accrual constraints necessary?. (12th June 2017) - Chatterjee, Punya; Karray, Salma; Sigué, Simon Pierre
Abstract: This paper investigates how the use of an accrual constraint in a cooperative advertising program affects channel members' profits in a bilateral monopoly, as well as their pricing and advertising decisions. The main findings indicate that, compared to unconstrained cooperative advertising programs, when an accrual constraint is used and the manufacturer's contribution to the retailer's advertising costs exceeds the accrued cooperative advertising budget, the retailer reduces both her retail price and advertising efforts to the level where cooperative advertising is not offered; while the manufacturer also reduces his wholesale price and advertising efforts, but this time, the wholesale price remains higher than when there is no cooperative advertising. These strategic moves translate to less (more) profits for the manufacturer (retailer). The use of an accrual constraint is counterproductive for the manufacturer as the retailer uses the accrued advertising fund as a side payment rather than a direct incentive to invest more in advertising. The manufacturer and retailer are better off when unconstrained cooperative advertising programs are supplemented with other incentives, including side payments and advertising support services.